We Shall Return! : MacArthur's Commanders and the Defeat of Japan, 1942-1945 - Leary, William M. (William Matthew), 1934-2006 (Book collections on Project MUSE., 2004)
They were the forgotten commanders of World War II. While the names of Bradley and Patton became household words for Americans, few could identify Krueger or Eichelberger. They served under General Douglas MacArthur, a military genius with an enormous ego who dominated publicity from the Southwest Pacific during the American advance from Australia, through New Guinea, to the Philippines. While people at home read about the great victories that were won by ""MacArthur's navy"" and ""MacArthur's air force, "" his subordinates labored in obscurity, fearful lest attention from the press lead to the.